Public Health and Primary Care - Rick Mayes PhD; Sean McKenna MD (SAGE Publishing, 2011)
Why are the goals of public health and primary care less politically popular and financially supported than those of curative medicine? A major part of the answer to this question lies in the fact that humans often worry wrongly by assessing risk poorly. This reality is a significant obstacle to the adequate promotion of and investment in public health, primary care, and prevention. Also, public health's tendency to infringe on personal privacy-as well as to call for difficult behavioral change-often sparks intense controversy and interest group opposition that discourage broader political support. Finally, in contrast to curative medicine, both the cost-benefit structure of public health (costs now, benefits later) and the way in which the profession operates make it largely invisible to and, thus, underappreciated by the general public. When curative medicine works well, most everybody notices. When public health and primary care work well, virtually nobody notices.